CATALYST, METHOD FOR PRODUCING CATALYST, AND METHOD FOR PRODUCING α,β-UNSATURATED ALDEHYDE, α,β-UNSATURATED CARBOXYLIC ACID, AND α,β-UNSATURATED CARBOXYLIC ACID ESTER

By optimizing the bismuth composition on the surface of a molybdenum-bismuth catalyst, high selectivity for α,β-unsaturated aldehydes and α,β-unsaturated carboxylic acids is achieved, addressing the performance and selectivity issues of existing catalysts.

JP7647872B2Active Publication Date: 2025-03-18MITSUBISHI CHEM CORP

Patent Information

Application Number
JP2023509243
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-24
Filing Date
2022-03-23
Publication Date
2025-03-18
Estimated Expiration
2042-03-23

AI Technical Summary

Technical Problem

Existing catalysts for producing α,β-unsaturated aldehydes and α,β-unsaturated carboxylic acids suffer from insufficient performance and high by-product formation, leading to reduced selectivity.

Method used

A catalyst comprising at least molybdenum and bismuth, with a specific bismuth composition on the catalyst surface relative to the entire catalyst, as determined by ICP and XPS analysis, within the ratio range of 1.3 to 5.

Benefits of technology

The catalyst achieves high selectivity for target products such as α,β-unsaturated aldehydes and α,β-unsaturated carboxylic acids, while minimizing by-product formation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647872000001
    Figure 0007647872000001
Patent Text Reader

Abstract

The purpose of the present invention is to provide a catalyst that has a high selectivity for α,β-unsaturated aldehydes, α,β-unsaturated carboxylic acids, and the like. This catalyst includes at least molybdenum and bismuth, and exhibits a B / A of 1.3-5, where A represents the ratio of the quantity of bismuth atoms with respect to the quantity of molybdenum atoms, calculated by an inductively coupled radiofrequency plasma (ICP) emission spectrography, and B represents the ratio of the peak area of bismuth atoms with respect to the peak area of molybdenum atoms, measured by an X-ray photoelectron spectroscopy analysis method.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a catalyst, a method for producing the catalyst, and a method for producing an α,β-unsaturated aldehyde, an α,β-unsaturated carboxylic acid, and an α,β-unsaturated carboxylic acid ester. [Background technology]

[0002] Methods for producing α,β-unsaturated aldehydes, α,β-unsaturated carboxylic acids, etc., are known, in which organic compounds such as propylene, isobutylene, t-butyl alcohol, and methyl t-butyl ether are subjected to a gas-phase oxidation reaction in the presence of a metal oxide catalyst.

[0003] For example, Patent Document 1 describes a method for producing a composite oxide catalyst containing at least molybdenum, bismuth, cobalt and / or nickel, and iron, as a method for producing a catalyst used in producing the corresponding unsaturated aldehyde and unsaturated carboxylic acid from an olefin. Furthermore, Patent Document 2 describes an example in which a catalyst for synthesizing unsaturated aldehydes and unsaturated carboxylic acids having excellent catalytic activity and selectivity can be provided, which is made of particles of a composite oxide containing at least molybdenum, iron, and cobalt, and in which the atomic ratios in the bulk composition and surface composition of the particles satisfy specific conditions. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2005-169311 A [Patent Document 2] JP 2011-115681 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, according to the study by the present inventors, it has been found that the catalysts described in Patent Documents 1 and 2 do not necessarily have sufficient performance and may produce many by-products. These problems affect the selectivity of α,β-unsaturated aldehydes and α,β-unsaturated carboxylic acids, and therefore, the reality is that further improvement in catalyst performance is desired. Therefore, from the viewpoint of further improving catalyst performance, it is required to control the catalyst properties. The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a catalyst which has a high selectivity for target products such as α,β-unsaturated aldehydes and α,β-unsaturated carboxylic acids. [Means for solving the problem]

[0006] The present inventors have conducted extensive research to achieve the above object, and as a result have found that in a catalyst containing at least molybdenum and bismuth, the target product can be produced with high selectivity by adjusting the bismuth composition on the catalyst surface relative to the entire catalyst. That is, the present invention includes the following.

[0007] [1]: A catalyst containing at least molybdenum and bismuth, A catalyst in which the ratio of the amount of bismuth atoms to the amount of molybdenum atoms calculated by ICP (inductively coupled plasma) atomic emission spectroscopy is A and the ratio of the peak area of ​​bismuth atoms to the peak area of ​​molybdenum atoms measured by X-ray photoelectron spectroscopy is B / A is 1.3 to 5. [2]: The catalyst according to [1], wherein the value of B / A is 1.5 to 4. [3]: The catalyst according to [1] or [2], wherein the value of B / A is 1.7 to 3. [4]: The catalyst according to any one of [1] to [3], wherein the value of A is 0.02 to 0.1. [5]: The catalyst according to any one of [1] to [4], wherein the value of B is 0.04 to 0.2. [6]: The catalyst according to any one of [1] to [5], wherein the value of B is 0.07 to 0.16. [7]: The catalyst according to any one of [1] to [6], which is used in producing an α,β-unsaturated aldehyde and / or an α,β-unsaturated carboxylic acid from an alkene, an alcohol or an ether. [8]: The catalyst according to any one of [1] to [7], wherein the catalyst composition is represented by the following formula (1): Mo a Bi b Fe c M d X e Y f S g O h (1) (In the formula (1), Mo, Bi, Fe, Si, and O represent molybdenum, bismuth, iron, silicon, and oxygen, respectively. M represents at least one element selected from the group consisting of cobalt and nickel. X represents at least one element selected from the group consisting of zinc, chromium, lead, manganese, calcium, magnesium, niobium, silver, barium, tin, tantalum, tungsten, antimony, phosphorus, boron, sulfur, selenium, tellurium, cerium, and titanium. Y represents at least one element selected from the group consisting of cesium, lithium, sodium, potassium, rubidium, and thallium. a, b, c, d, e, f, g, and h represent atomic ratios of each element, and when a=12, b=0.01-3, c=0-8, d=0-12, e=0-8, f=0.001-2, and g=0-20, and h represents an oxygen atomic ratio required to satisfy the atomic valence of each of the components.) [9]: A method for producing a catalyst containing at least molybdenum and bismuth, comprising the following steps (i) to (v): (i) mixing at least a molybdenum raw material and a bismuth raw material with a solvent to obtain a slurry (liquid A); (ii) stirring the liquid A for 20 to 90 minutes at a temperature 1 to 30° C. lower than the boiling point of the solvent to obtain a slurry (liquid B); (iii) stirring the liquid B for 10 minutes to 10 hours at a temperature at least 2° C. higher than the temperature in the step (ii) to obtain a slurry (liquid C); (iv) drying the liquid C to obtain a dry product; (v) A step of calcining the dried product to obtain a catalyst.

[10] : The method for producing a catalyst according to [9], wherein in the step (i), 50 mass % or more of the total solvent is water.

[11] : The method for producing a catalyst according to [9] or

[10] , wherein the temperature in the step (iii) is 1 to 20° C. higher than the boiling point of the solvent.

[12] : The method for producing a catalyst according to any one of [9] to

[11] , wherein in the step (iii), the solution B is stirred for 90 minutes to 10 hours to obtain the solution C.

[13] : A method for producing a catalyst according to any one of [9] to

[12] , which produces a catalyst used in producing an α,β-unsaturated aldehyde and / or an α,β-unsaturated carboxylic acid from an alkene, an alcohol or an ether.

[14] : A method for producing a catalyst according to any one of [9] to

[13] , which comprises producing a catalyst having a composition represented by the following formula (1): Mo a Bi b Fe c M d X e Y f S g O h (1) (In the formula (1), Mo, Bi, Fe, Si, and O respectively represent molybdenum, bismuth, iron, silicon, and oxygen; M represents at least one element selected from the group consisting of cobalt and nickel; X represents at least one element selected from the group consisting of zinc, chromium, lead, manganese, calcium, magnesium, niobium, silver, barium, tin, tantalum, tungsten, antimony, phosphorus, boron, sulfur, selenium, tellurium, cerium, and titanium; and Y represents at least one element selected from the group consisting of cesium, lithium, sodium, potassium, rubidium, and thallium. a, b, c, d, e, f, g, and h represent atomic ratios of each element, and when a=12, b=0.01-3, c=0-8, d=0-12, e=0-8, f=0.001-2, and g=0-20, and h represents an oxygen atomic ratio required to satisfy the atomic valence of each of the components.)

[15] : A method for producing an α,β-unsaturated aldehyde and / or an α,β-unsaturated carboxylic acid from an alkene, an alcohol or an ether using the catalyst according to any one of [1] to [8].

[16] : A method for producing an α,β-unsaturated aldehyde and / or an α,β-unsaturated carboxylic acid from an alkene, an alcohol or an ether using a catalyst produced by the method for producing a catalyst according to any one of [9] to

[14] .

[17] : A method for producing an α,β-unsaturated carboxylic acid, comprising producing an α,β-unsaturated carboxylic acid from an α,β-unsaturated aldehyde produced by the method according to

[15] or

[16] .

[18] : A method for producing an α,β-unsaturated carboxylic acid ester, comprising producing an α,β-unsaturated carboxylic acid ester from an α,β-unsaturated carboxylic acid produced by the production method according to any one of

[15] to

[17] . Effect of the Invention

[0008] According to the present invention, a catalyst having a high selectivity for the target product can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, the embodiments of the present invention will be described below, but the present invention is not limited to the following. Furthermore, the description of "XX or more and YY or less" or "XX to YY" representing a numerical range means a numerical range including a lower limit and an upper limit which are the endpoints, unless otherwise specified. When a numerical range is described in stages, the upper limit and the lower limit of each numerical range can be arbitrarily combined.

[0010] [catalyst] The catalyst according to the present invention is a catalyst containing at least molybdenum and bismuth, in which, when A is the ratio of the amount of bismuth atoms to the amount of molybdenum atoms calculated by ICP (inductively coupled plasma) emission spectroscopy, and B is the ratio of the peak area of ​​bismuth atoms to the peak area of ​​molybdenum atoms measured by X-ray photoelectron spectroscopy, B / A is 1.3 to 5. By using such a catalyst, the target product can be produced from the raw material with high selectivity. From the viewpoint of the selectivity of the target product, the catalyst according to the present invention is preferably an oxidation catalyst, and more preferably a catalyst used in producing an α,β-unsaturated aldehyde and / or an α,β-unsaturated carboxylic acid. Specifically, the catalyst is preferably a catalyst for producing an α,β-unsaturated aldehyde and / or an α,β-unsaturated carboxylic acid from an alkene, an alcohol, or an ether. Note that "producing an α,β-unsaturated aldehyde and / or an α,β-unsaturated carboxylic acid" means that either one of an α,β-unsaturated aldehyde and an α,β-unsaturated carboxylic acid or both may be produced.

[0011] (Catalyst Composition) The catalyst according to the present invention contains at least molybdenum and bismuth, and preferably has a composition represented by the following formula (1): The catalyst components may contain small amounts of elements not represented in the following formula (1). Mo a Bi b Fe c M d X e Y f S g O h (1) In formula (1), Mo, Bi, Fe, Si, and O represent molybdenum, bismuth, iron, silicon, and oxygen, respectively. M represents at least one element selected from the group consisting of cobalt and nickel. X represents at least one element selected from the group consisting of zinc, chromium, lead, manganese, calcium, magnesium, niobium, silver, barium, tin, tantalum, tungsten, antimony, phosphorus, boron, sulfur, selenium, tellurium, cerium, and titanium. Y represents at least one element selected from the group consisting of cesium, lithium, sodium, potassium, rubidium, and thallium. a, b, c, d, e, f, g, and h represent the atomic ratio of each element, and when a=12, b=0.01-3, c=0-8, d=0-12, e=0-8, f=0.001-2, and g=0-20, and h represents the oxygen atomic ratio required to satisfy the atomic valence of each component.

[0012] In the formula (1), from the viewpoint of improving the selectivity of the target product, when a=12, the lower limit of b is preferably 0.03 or more, and more preferably 0.05 or more. The upper limit of b is preferably 2 or less, and more preferably 1 or less. The lower limit of c is preferably 0.01 or more, more preferably 0.1 or more, even more preferably 1 or more, and particularly preferably 3 or more. The upper limit of c is preferably 6 or less, and more preferably 4 or less.

[0013] The catalyst contains molybdenum, bismuth, and, if necessary, iron, and may contain other elements other than these elements, such as the M element, the X element, and the Y element in the formula (1). Of the other elements, it is preferable that the catalyst contains the M element, and it is more preferable that the catalyst also contains the Y element.

[0014] In the formula (1), from the viewpoint of improving the selectivity of the target product, when a=12, the lower limit of d is preferably 0.01 or more, more preferably 0.1 or more, even more preferably 1 or more, and particularly preferably 3 or more. The upper limit of d is preferably 10 or less, more preferably 9 or less. The lower limit of e is preferably 0.1 or more, more preferably 0.2 or more, and even more preferably 0.5 or more. The upper limit of e is preferably 6 or less, more preferably 4 or less. The lower limit of f is preferably 0.05 or more, more preferably 0.1 or more, and even more preferably 0.2 or more. The upper limit is preferably 1.8 or less, more preferably 1.6 or less, and even more preferably 1.4 or less.

[0015] The catalyst may also have a carrier for supporting the above elements. The carrier is not particularly limited, and examples thereof include silica, alumina, silica-alumina, magnesia, titania, silicon carbide, and the like. Among these, when a carrier is used, silica is preferred as the carrier in order to prevent the carrier itself from reacting. In the present invention, when a carrier is used in the catalyst, the carrier is also considered to be the catalyst.

[0016] In the above formula (1), when a=12, the upper limit of g is preferably 20 or less, more preferably 15 or less, and even more preferably 10 or less, from the viewpoint of improving the selectivity of the target product.

[0017] The composition of the catalyst is determined by analyzing the components obtained by dissolving the catalyst in ammonia water using ICP optical emission spectrometry. An example of an analytical device that can be used is an ICP Optima 8300 (manufactured by Perkin Elmer). The analytical conditions are: power: 1300 W, plasma gas flow rate: 10 L / min, auxiliary gas flow rate: 0.2 L / min, nebulizer gas flow rate: 0.55 L / min, and detector: segmented array type CCD. ICP optical emission spectrometry is a method in which atoms contained in a sample are excited when plasma energy is applied from the outside, and the spectral lines emitted when the excited atoms return to a lower energy level are measured.

[0018] (Bismuth composition of catalyst surface relative to entire catalyst) In the catalyst according to the present invention, when A is the ratio of the amount of bismuth atoms to the amount of molybdenum atoms calculated by ICP emission spectroscopy, and B is the ratio of the peak area of ​​bismuth atoms to the peak area of ​​molybdenum atoms measured by X-ray photoelectron spectroscopy, B / A is 1.3 to 5. Here, A represents the ratio of the amount of bismuth atoms to the amount of molybdenum atoms in the entire catalyst, and B represents the ratio of the amount of bismuth atoms to the amount of molybdenum atoms on the catalyst surface. In other words, B / A represents the amount of bismuth atoms present on the catalyst surface to the amount of bismuth atoms in the entire catalyst. When the B / A of the catalyst satisfies the above range, the target product can be produced from the raw material with high selectivity. The reason for this is not clear, but the following is thought to be the case. Bismuth acts as an active site for the reaction on the catalyst surface, and when B / A is 1.3 or more, that is, when there is a sufficient amount of bismuth atoms present on the catalyst surface, the selective oxidation reaction to the target product proceeds, improving the selectivity of the target product. In addition, when B / A is 5 or less, that is, when there are not an excess of bismuth atoms present on the catalyst surface, it is thought that successive reactions from the target product are suppressed, and a decrease in the selectivity of the target product is suppressed. Among the above, the lower limit of the B / A value is preferably 1.5 or more, more preferably 1.7 or more, and even more preferably 1.9 or more. The upper limit of the B / A value is preferably 4 or less, and more preferably 3 or less. The lower limit of the value of A is preferably 0.02 or more, and more preferably 0.03 or more, and the upper limit of the value of A is preferably 0.1 or less, and more preferably 0.09 or less. The lower limit of the value of B is preferably 0.04 or more, more preferably 0.06 or more, and even more preferably 0.07 or more, while the upper limit of the value of B is preferably 0.2 or less, more preferably 0.18 or less, and even more preferably 0.16 or less.

[0019] Methods for controlling the values ​​of A, B, and B / A include, in the catalyst production method, methods for adjusting the type and amount of molybdenum raw material, the type and amount of bismuth raw material, stirring time, heating time, heating temperature, etc. Among these, in particular, in step (ii) described below, stirring is performed for 20 to 90 minutes at a temperature 1 to 30° C. lower than the boiling point of the solvent, and in step (iii), stirring is performed for 10 minutes to 10 hours at a temperature 2° C. or higher than the boiling point of the solvent, whereby the values ​​of A, B, and B / A can be controlled within the desired ranges.

[0020] In the present invention, the value of A is obtained by performing ICP emission analysis of the catalyst as described above and calculating the ratio of the amount of bismuth atoms to the amount of molybdenum atoms. The value of B is obtained by performing X-ray photoelectron spectroscopy of the catalyst and calculating the ratio of the peak area of ​​bismuth atoms to the peak area of ​​molybdenum atoms. For example, a Quantera II (manufactured by ULVAC-PHI, Inc.) can be used as the analysis device. The analysis conditions are X-ray: HP mode - monochromatic Al source, output: 300 W, take-in angle: 45°, and the X-ray beam diameter is 100 μmφ and linearly scans a range of 1400 μm. X-ray photoelectron spectroscopy is a method of measuring the composition and chemical state of elements constituting the sample surface by irradiating the sample surface with X-rays and measuring the kinetic energy of photoelectrons emitted from the sample surface. In general, information on elements present within a few nm of the sample surface can be obtained, so that information on the composition and chemical state of the catalyst surface can be obtained.

[0021] (catalyst density) The density of the catalyst is not particularly limited, but from the viewpoint of improving the durability of the catalyst, the lower limit is 0.2 g / cm 3 It is preferable that the content is 0.5 g / cm or more. 3 More preferably, it is 1 g / cm or more. 3 On the other hand, from the viewpoint of improving the selectivity of the target product, the upper limit is 50 g / cm. 3 It is preferable that the thickness is less than 30 g / cm 3 More preferably, it is 20 g / cm or less. 3 It is even more preferable that:

[0022] [Catalyst manufacturing method] Another embodiment of the present invention is a method for producing a catalyst containing at least molybdenum and bismuth, comprising the following steps (i) to (v). The obtained catalyst preferably has the above-mentioned B / A of 1.3 to 5. (i) A step of mixing at least a molybdenum raw material and a bismuth raw material with a solvent to obtain a slurry (liquid A). (ii) A step of stirring the liquid A for 20 to 90 minutes at a temperature 1 to 30° C. lower than the boiling point of the solvent to obtain a slurry (liquid B). (iii) A step of stirring the liquid B at a temperature at least 2° C. higher than the temperature in the step (ii) for 10 minutes to 10 hours to obtain a slurry (liquid C). (iv) A step of drying the liquid C to obtain a dry product. (v) A step of calcining the dried product to obtain a catalyst. The method for producing a catalyst according to the present invention may further include a molding step, which will be described later. Each step will be described in detail below.

[0023] (Step (i)) In step (i), at least a molybdenum raw material and a bismuth raw material are mixed with a solvent to obtain a slurry (liquid A). Liquid A is prepared by mixing raw materials of molybdenum and bismuth with a solvent. Raw materials of each element included in the formula (1) (hereinafter also referred to as catalyst raw materials) may be further mixed. The amount of the catalyst raw material used may be appropriately adjusted so as to obtain a desired catalyst composition. The catalyst raw material is not particularly limited, and nitrates, carbonates, hydrogen carbonates, acetates, ammonium salts, sulfates, oxides, chlorides, hydroxides, halides, oxoacids, oxoacid salts, etc. of each element can be used alone or in combination of two or more kinds.

[0024] Examples of the molybdenum raw material include ammonium paramolybdate, molybdenum trioxide, molybdic acid, molybdenum chloride, etc., and it is preferable to use ammonium paramolybdate. Examples of the bismuth raw material include bismuth nitrate, bismuth oxide, bismuth subcarbonate, etc., and it is preferable to use bismuth oxide. Examples of the iron raw material include iron nitrate, iron hydroxide, iron trioxide, etc., and it is preferable to use iron nitrate.

[0025] The solvent is not particularly limited as long as it can dissolve or disperse the catalyst raw materials, but it is preferable that the solvent contains at least water, more preferably 50 mass% or more of the total solvent is water, and even more preferably 80 mass% or more of the total solvent is water, and water alone may be used. The solvent may also contain an organic solvent. The organic solvent is not particularly limited, and examples thereof include alcohol and acetone. The amount of the solvent used is not particularly limited, but is preferably 30 to 400 parts by mass with respect to 100 parts by mass of the total catalyst raw materials.

[0026] The step (i) preferably includes the following steps (i-1) and (i-2).

[0027] (i-1) A step of preparing a solution or slurry (Liquid A1) containing molybdenum, bismuth, and the elements X and Y in formula (1), and a solution or slurry (Liquid A2) containing iron and the element M in formula (1). (ii-2) A step of mixing the A1 liquid and the A2 liquid to prepare the A liquid. Each step will be described in detail below.

[0028] <Process (i-1)> In step (i-1), a solution or slurry (Liquid A1) containing molybdenum, bismuth, and the X and Y elements in formula (1), and a solution or slurry (Liquid A2) containing iron and the M element in formula (1) are prepared. The order in which Liquid A1 and Liquid A2 are prepared is not limited, and Liquid A1 and Liquid A2 may be prepared simultaneously. The amount of each catalyst raw material used is preferably adjusted so that the resulting catalyst has the composition represented by the above formula (1). The amount of the solvent used is not particularly limited, but the amount of A1 solution is preferably 70 to 400 parts by mass per 100 parts by mass of the total catalyst raw materials, and the amount of A2 solution is preferably 30 to 230 parts by mass per 100 parts by mass of the total catalyst raw materials.

[0029] <Process (i-2)> In step (i-2), liquid A is prepared by mixing liquid A1 and liquid A2 obtained in step (i-1).

[0030] (Step (ii)) In step (ii), the liquid A obtained in step (i) is stirred for 20 to 90 minutes at a temperature 1 to 30° C. lower than the boiling point of the solvent to obtain a slurry (liquid B). For example, when water is used as the solvent in step (i), the boiling point of water is 100° C., so in step (ii), liquid A is stirred at 70 to 99° C. When multiple solvents with different boiling points are used in step (i), the mixture is stirred at a temperature 1 to 30° C. lower than the boiling point of the solvent with the largest mass ratio. In step (ii), when the catalyst raw material is dissolved in the solvent, the temperature and stirring time are set to the above conditions to adjust the solubility of the bismuth raw material to a constant value. As a result, when the bismuth molybdate composite oxide layer is formed in step (iii) described later, it is believed that bismuth, which serves as an active site, is suitably precipitated on the surface, and a catalyst having a B / A of 1.5 to 5 can be obtained. If the temperature in step (ii) is lower than the specified value or the stirring time is shorter than the specified value, the solubility of the bismuth raw material decreases, and the B / A of the resulting catalyst tends to be less than 1.5. On the other hand, if the temperature in step (ii) is higher than the specified value or the stirring time is longer than the specified value, the solubility of the molybdenum raw material and the bismuth raw material increases, and the B / A of the resulting catalyst tends to be greater than 5.

[0031] The upper limit of the temperature during stirring of Solution A is preferably at least 3° C. lower than the boiling point of the solvent, more preferably at least 5° C. lower, and the lower limit is preferably at most 25° C. lower than the boiling point of the solvent, more preferably at most 20° C. lower, and even more preferably at most 10° C. lower.

[0032] The lower limit of the stirring time in the above-mentioned temperature range is preferably 30 minutes or more, more preferably 40 minutes or more, and the upper limit is preferably 80 minutes or less, more preferably 70 minutes or less.

[0033] (Step (iii)) In the step (iii), the liquid B obtained in the step (ii) is stirred for 10 minutes to 10 hours at a temperature that is at least 2° C. higher than the temperature in the step (ii) to obtain a slurry (liquid C). In step (iii), a bismuth molybdate composite oxide layer is formed. At this time, by stirring the B solution in which the solubility of bismuth is adjusted in step (ii) at the above-mentioned temperature for the above-mentioned time, it is considered that when the bismuth molybdate composite oxide layer is formed, the bismuth that serves as the active site is suitably precipitated on the surface, and a catalyst having a B / A of 1.5 to 5 can be obtained. If the temperature in step (iii) is lower than the specified value or the stirring time is shorter than the specified value, the precipitation of bismuth on the surface is not promoted, and the B / A of the obtained catalyst tends to be less than 1.5. On the other hand, if the temperature in step (iii) is higher than the specified value or the stirring time is longer than the specified value, the precipitation of bismuth on the surface becomes excessive, and the B / A of the obtained catalyst tends to be greater than 5.

[0034] The lower limit of the temperature during stirring of Solution B is preferably at least 3° C. higher than the temperature in step (ii), more preferably at least 5° C. higher, even more preferably at least 6° C. higher, and particularly preferably at least 8° C. higher. The upper limit is preferably at most 20° C. higher, more preferably at most 10° C. higher than the temperature in step (ii). The temperature at which Liquid B is stirred is preferably 1 to 20°C higher than the boiling point of the solvent. For example, when water is used as the solvent in step (i), the boiling point of water is 100°C, so it is preferable to stir Liquid B at 101 to 120°C in step (iii). The lower limit of the temperature at which Liquid B is stirred is more preferably 2°C or higher, and even more preferably 3°C or higher, than the boiling point of the solvent. The upper limit is more preferably 10°C or lower, and even more preferably 5°C or lower than the boiling point of the solvent.

[0035] The lower limit of the stirring time in the above-mentioned temperature range is preferably 20 minutes or more, more preferably 30 minutes or more, even more preferably 60 minutes or more, particularly preferably 90 minutes or more, and most preferably 2 hours or more, and the upper limit is preferably 9 hours or less, more preferably 8 hours or less.

[0036] (Step (iv)) In the step (iv), the liquid C obtained in the step (iii) is dried to obtain a dry product. Liquid C can be dried by known methods such as drum drying, flash drying, evaporation to dryness, spray drying, etc. The drying temperature is preferably 120 to 500°C, more preferably a lower limit of 140°C or more and an upper limit of 350°C or less. Drying is preferably carried out so that the moisture content of the resulting dried material is 0.1 to 4.5% by mass. These conditions can be appropriately selected depending on the shape and size of the desired catalyst. By drying Liquid C, adhesion of the dried material can be suppressed and the yield can be improved.

[0037] (Process (v)) In step (v), the dried product obtained in step (iv) is calcined to obtain a catalyst. Calcination can be performed after the molding step described below to obtain a molded product, but from the viewpoint of catalyst strength, it is preferable to perform the calcination before the molding step. In the present invention, the calcined and molded products are collectively referred to as catalysts. The calcination may be performed only once, or may be performed several times in combination with the molding step described later. For example, the primary calcination may be performed first, the resulting primary calcination product may be subjected to the molding step described later, and the resulting molded product may be subjected to the secondary calcination. Alternatively, the primary calcination and the secondary calcination may be performed, and the resulting catalyst may be subjected to the molding step. The calcination is preferably carried out under a flow of an oxygen-containing gas such as air, or under a flow of an inert gas. An "inert gas" refers to a gas that does not reduce the catalytic activity, such as nitrogen, carbon dioxide, helium, and argon.

[0038] The firing temperature is preferably 200 to 700° C. The lower limit of the firing temperature is more preferably 300° C. or higher, while the upper limit is more preferably 500° C. or lower, and further preferably 450° C. or lower. The firing time is preferably 0.5 to 40 hours, and the lower limit is more preferably 1 hour or more. The firing time means the time during which a predetermined firing temperature is maintained after the temperature is reached.

[0039] Among the above, it is preferable to perform a primary firing on the dried product, followed by molding, and then perform a secondary firing on the resulting molded product. In this case, the firing temperature of the primary firing is preferably 200 to 600°C, more preferably 250°C or more at the lower limit and 450°C or less at the upper limit. The firing time of the primary firing is preferably 0.5 to 5 hours from the viewpoint of improving the selectivity of the target product. The type and method of the firing furnace in the primary firing are not particularly limited, and for example, a box-type firing furnace, a tunnel-type firing furnace, or the like may be used to fire the dried or molded material in a fixed state. In addition, a rotary kiln or the like may be used to fire the dried or molded material while it is being fluidized.

[0040] The calcination temperature of the secondary calcination is preferably 300 to 700°C, more preferably 400°C or more at the lower limit and 600°C or less at the upper limit. From the viewpoint of improving the selectivity of the target product, the calcination time of the secondary calcination is preferably 10 minutes to 10 hours, more preferably 1 hour or more at the lower limit. The type of calcination device and method for the secondary calcination are not particularly limited, and the molded product or the primary calcined product may be calcined in a fixed state using, for example, a box-type calcination furnace, a tunnel-type calcination furnace, or the like. In addition, the molded product or the primary calcined product may be calcined while being fluidized using a rotary kiln, or the like.

[0041] (molding process) In the molding step, the dried product obtained in the step (iv) or the fired product obtained in the step (v) is molded to obtain a molded product. The molding method is not particularly limited, and a known dry or wet molding method can be applied. For example, tablet molding, extrusion molding, pressure molding, rolling granulation, etc. can be mentioned. During molding, conventionally known additives, for example, organic compounds such as polyvinyl alcohol and carboxymethyl cellulose, etc., and inorganic compounds such as graphite and diatomaceous earth, and inorganic fibers such as glass fibers, ceramic fibers and carbon fibers, may be added.

[0042] The shape of the molded product is not particularly limited, and may be any shape such as a sphere, a cylinder, a ring, a star, or a granule shape crushed and classified after molding. Among these, from the viewpoint of mechanical strength, a sphere, a cylinder, or a ring is preferable. The size of the molded product is not particularly limited, but for example, in the case of a sphere, the diameter of the sphere is preferably 0.1 to 10 mm. The lower limit of the diameter of the sphere is more preferably 0.5 mm or more, more preferably 1 mm or more, and particularly preferably 3 mm or more. The upper limit of the diameter of the sphere is more preferably 8 mm or less, and even more preferably 6 mm or less. In the case of a ring or cylinder, the diameter and height of the circle at the bottom of the ring or cylinder are both preferably 0.1 to 10 mm. The lower limits of the diameter and height are more preferably 0.5 mm or more, more preferably 1 mm or more, and particularly preferably 3 mm or more. The upper limits of the diameter and height are more preferably 8 mm or less, and even more preferably 6 mm or less. In the case of other shapes, the length between the two most distant points in the solid of the catalyst is preferably 0.1 to 10 mm. The lower limit of the length between the two points is more preferably 0.5 mm or more, even more preferably 1 mm or more, and particularly preferably 3 mm or more. The upper limit of the length between the two points is more preferably 8 mm or less, and even more preferably 6 mm or less. This improves the selectivity of the target product and the catalyst life.

[0043] The outer surface area of ​​the molded product is not particularly limited, but from the viewpoint of stable production of the target product over a long period of time, the lower limit is 0.01 cm 2 More than 0.05cm is preferable. 2 More than 0.1 cm is preferable. 2 On the other hand, from the viewpoint of improving the selectivity of the target product, the upper limit is 4 cm 2 Less than 3cm is preferable 2 Less than 2cm is preferable. 2 The following is even more preferred:

[0044] The volume of the molded product is not particularly limited, but from the viewpoint of stably producing the target product over a long period of time, the lower limit is 0.0002 cm 3 More than 0.002 cm is preferable. 3 More preferably, 0.02 cm or more 3On the other hand, from the viewpoint of improving the selectivity of the target product, the upper limit is 5 cm 3 Less than 1cm is preferable 3 Less than 0.5cm is preferable 3 The following is even more preferred:

[0045] The mass of the molded product is not particularly limited, but from the viewpoint of stable production of the target product over a long period of time, the lower limit is preferably 0.002 g / piece or more, more preferably 0.01 g / piece or more, and even more preferably 0.05 g / piece or more, while from the viewpoint of improving the selectivity of the target product, the upper limit is preferably 0.5 g / piece or less, more preferably 0.3 g / piece or less, and even more preferably 0.2 g / piece or less.

[0046] The packed bulk density of the molded product is not particularly limited, but from the viewpoint of stably producing the target product over a long period of time, the lower limit is 0.2 g / cm. 3 More than 0.3 g / cm is preferable. 3 More preferably, 0.4 g / cm 3 On the other hand, from the viewpoint of improving the selectivity of the target product, the upper limit is 1 g / cm 3 Less than 0.9 g / cm is preferred. 3 Less than 0.8 g / cm is more preferable. 3 The following is even more preferable: The packed bulk density of the molded product means a value calculated from the total mass of the molded product when the molded product is packed into a 100 ml measuring cylinder by a method conforming to JIS-K 7365.

[0047] The obtained molded product may be supported on a carrier. Examples of the carrier used for supporting include silica, alumina, silica-alumina, magnesia, titania, silicon carbide, etc. The molded product may also be used after being diluted with an inert substance such as silica, alumina, silica-alumina, magnesia, titania, silicon carbide, etc. In this manner, the catalyst can be produced.

[0048] [Method for producing α,β-unsaturated aldehyde and / or α,β-unsaturated carboxylic acid] In the method for producing an α,β-unsaturated aldehyde and / or an α,β-unsaturated carboxylic acid according to the present invention, the corresponding α,β-unsaturated aldehyde and / or α,β-unsaturated carboxylic acid is produced from an alkene, an alcohol or an ether using the catalyst according to the present invention or a catalyst produced by the production method according to the present invention.

[0049] Examples of the alkene include propylene and isobutylene. Examples of the alcohol include t-butyl alcohol and isobutyl alcohol. Examples of the ether include methyl t-butyl ether. By oxidizing these raw organic compounds, the corresponding α,β-unsaturated aldehyde and / or α,β-unsaturated carboxylic acid can be produced. For example, when the raw organic compound is propylene, the corresponding α,β-unsaturated aldehyde is acrolein, and the corresponding α,β-unsaturated carboxylic acid is acrylic acid. When the raw organic compound is isobutylene, t-butyl alcohol, isobutyl alcohol, or methyl t-butyl ether, the corresponding α,β-unsaturated aldehyde is methacrolein, and the corresponding α,β-unsaturated carboxylic acid is methacrylic acid. From the viewpoint of the selectivity of the target product, it is preferable that the α,β-unsaturated aldehyde and the α,β-unsaturated carboxylic acid are methacrolein and methacrylic acid, respectively.

[0050] The method for producing an α,β-unsaturated aldehyde and / or an α,β-unsaturated carboxylic acid according to the present invention can be carried out by contacting the catalyst according to the present invention or the catalyst produced by the production method according to the present invention with the raw material organic compound and a raw material gas containing oxygen in a reactor.

[0051] The reactor is not particularly limited, but it is preferable to use a tubular reactor equipped with a reaction tube filled with a catalyst, and industrially, it is more preferable to use a multi-tubular reactor equipped with a plurality of reaction tubes. The catalyst layer in the reactor may be a single layer, or a plurality of catalysts with different activities may be packed separately in a plurality of layers. In addition, the catalyst may be diluted with an inert carrier and packed in order to control the activity.

[0052] The concentration of the raw material organic compound in the raw material gas is preferably 1 to 20% by volume, more preferably 3% by volume or more and 10% by volume or less. The raw material organic compound may contain a small amount of impurities such as lower saturated alkanes that do not substantially affect the reaction.

[0053] The oxygen concentration in the raw material gas is preferably 0.1 to 5 moles per mole of the raw material organic compound, with the lower limit being 0.5 moles or more and the upper limit being 3 moles or less. From the viewpoint of economic efficiency, it is preferable to use air as the oxygen source of the raw material gas. If necessary, a gas enriched with oxygen by mixing pure oxygen with air or the like may be used. From the viewpoint of economy, the raw material gas may be diluted with an inert gas such as nitrogen or carbon dioxide. Furthermore, water vapor may be added to the raw material gas. By carrying out the reaction in the presence of water vapor, α,β-unsaturated aldehyde and / or α,β-unsaturated carboxylic acid can be obtained with higher selectivity. The concentration of water vapor in the raw material gas is preferably 0.1 to 50% by volume, and more preferably the lower limit is 1% by volume or more and the upper limit is 40% by volume or less.

[0054] The reaction pressure is preferably 0 to 1 MPa (G). Here, "(G)" is a gauge pressure, and 0 MPa (G) means that the reaction pressure is atmospheric pressure. The reaction temperature is preferably 200 to 450°C, and more preferably the lower limit is 250°C or more and the upper limit is 400°C or less. The contact time between the raw material gas and the catalyst is preferably 0.5 to 15 seconds. The lower limit of the contact time is more preferably 1 second or more, while the upper limit is more preferably 10 seconds or less, and further preferably 5 seconds or less.

[0055] By carrying out the production as described above, an α,β-unsaturated aldehyde and / or an α,β-unsaturated carboxylic acid corresponding to the raw material organic compound used can be obtained with high selectivity.

[0056] [Method of producing α,β-unsaturated carboxylic acid] In the method for producing an α,β-unsaturated carboxylic acid according to the present invention, a corresponding α,β-unsaturated carboxylic acid or the like is produced from an α,β-unsaturated aldehyde produced by the production method according to the present invention.

[0057] Examples of the α,β-unsaturated aldehyde include (meth)acrolein, crotonaldehyde (β-methylacrolein), and cinnamaldehyde (β-phenylacrolein). The α,β-unsaturated carboxylic acid produced is an α,β-unsaturated carboxylic acid in which the aldehyde group of the α,β-unsaturated aldehyde is changed to a carboxyl group. Specifically, when the α,β-unsaturated aldehyde is (meth)acrolein, (meth)acrylic acid is obtained. From the viewpoint of the selectivity of the target product, the α,β-unsaturated aldehyde and the α,β-unsaturated carboxylic acid are preferably (meth)acrolein and (meth)acrylic acid, respectively, and more preferably methacrolein and methacrylic acid. Note that "(meth)acrolein" refers to acrolein and methacrolein, and "(meth)acrylic acid" refers to acrylic acid and methacrylic acid.

[0058] The method for producing an α,β-unsaturated carboxylic acid according to the present invention can be carried out by contacting the catalyst according to the present invention or the catalyst produced by the production method according to the present invention with a raw material gas containing an α,β-unsaturated aldehyde and oxygen in a reactor. As the catalyst, a heteropolyacid catalyst or the like is preferably used. As the reactor, the same reactor as that used in the above-mentioned method for producing an α,β-unsaturated aldehyde and / or an α,β-unsaturated carboxylic acid can be used. The catalyst layer in the reactor may be a single layer, or multiple catalysts with different activities may be packed separately in multiple layers. In addition, the catalyst may be diluted with an inert carrier and packed in order to control the activity.

[0059] The concentration of the α,β-unsaturated aldehyde in the raw material gas is preferably 1 to 20% by volume, more preferably 3% by volume or more and 10% by volume or less. The α,β-unsaturated aldehyde may contain a small amount of impurities such as lower saturated aldehydes that do not substantially affect the reaction.

[0060] The oxygen concentration in the raw material gas is preferably 0.4 to 4 moles per mole of α,β-unsaturated aldehyde, and more preferably 0.5 moles or more and 3 moles or less. From the viewpoint of economic efficiency, air is preferably used as the oxygen source of the raw material gas. If necessary, a gas enriched with oxygen by mixing pure oxygen with air or the like may be used.

[0061] From the viewpoint of economy, the raw material gas may be diluted with an inert gas such as nitrogen or carbon dioxide. Furthermore, water vapor may be added to the raw material gas. By carrying out the reaction in the presence of water vapor, α,β-unsaturated carboxylic acid can be obtained with higher selectivity. The concentration of water vapor in the raw material gas is preferably 0.1 to 50% by volume, and more preferably the lower limit is 1% by volume or more and the upper limit is 40% by volume or less.

[0062] The reaction pressure is preferably 0 to 1 MPa (G), and the reaction temperature is preferably 200 to 450° C., more preferably the lower limit is 250° C. or more and the upper limit is 400° C. or less. The contact time between the raw material gas and the catalyst is preferably 0.5 to 15 seconds. The lower limit of the contact time is more preferably 1 second or more, while the upper limit is more preferably 10 seconds or less, and further preferably 5 seconds or less.

[0063] [Method of producing α,β-unsaturated carboxylic acid ester] In the method for producing an α,β-unsaturated carboxylic acid ester according to the present invention, the α,β-unsaturated carboxylic acid produced by the method for producing the present invention is esterified. The alcohol to be reacted with the α,β-unsaturated carboxylic acid is not particularly limited, and examples thereof include methanol, ethanol, propanol, isopropanol, butanol, and isobutanol. Examples of the α,β-unsaturated carboxylic acid ester obtained include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, and isobutyl (meth)acrylate. The reaction can be carried out in the presence of an acid catalyst such as a sulfonic acid type cation exchange resin. The reaction temperature is preferably 50 to 200°C. EXAMPLES

[0064] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. In the examples and comparative examples, "parts" means parts by mass.

[0065] (Catalyst Composition) The overall composition of the catalyst was determined by dissolving the catalyst in ammonia water and analyzing the components by ICP emission spectrometry. The analyzer used was an ICP Optima 8300 (Perkin Elmer), with an output of 1300 W, plasma gas flow rate of 10 L / min, auxiliary gas flow rate of 0.2 L / min, nebulizer gas flow rate of 0.55 L / min, and detector: segmented array CCD. In addition, the value of A was calculated from the ratio of the amount of bismuth atoms to the amount of molybdenum atoms in the overall composition of the obtained catalyst.

[0066] (X-ray photoelectron spectroscopy of catalyst) The value of B was obtained by performing X-ray photoelectron spectroscopy of the catalyst and calculating the ratio of the peak area of ​​bismuth atoms to the peak area of ​​molybdenum atoms. The analyzer used was a Quantera II (ULVAC-PHI, Inc.), with X-ray: HP mode - monochromatic Al source, output: 300 W, and acceptance angle: 45°, and the X-ray beam diameter was 100 μmφ, linearly scanning a range of 1400 μm.

[0067] (Reaction evaluation) The reaction evaluation of the catalyst in the examples and comparative examples was carried out using the production of methacrolein and methacrylic acid by oxidation of isobutylene as an example. The raw material gas and the product in the reaction evaluation were analyzed using the following gas chromatography. Analysis of methacrolein: Shimadzu GC-2014, column: QUADREX 007-CW 20m x 0.32mm, film thickness: 3μm Analysis of methacrylic acid: Shimadzu GC-2014, column: J&W DB-FFAP, 30 m x 0.32 mm, film thickness 1.00 μm From the results of gas chromatography, the total selectivity of the produced methacrolein and methacrylic acid was calculated according to the following formula. Total selectivity of methacrolein and methacrylic acid (%) = (P1 + P2) / M1 × 100 In the above formula, M1 is the number of moles of isobutylene reacted per unit time, P1 is the number of moles of methacrolein produced per unit time, and P2 is the number of moles of methacrylic acid produced per unit time.

[0068] <Example 1> A1 liquid was obtained by mixing 500 parts by mass of ammonium paramolybdate tetrahydrate, 12.3 parts by mass of ammonium paratungstate, 27.6 parts by mass of cesium nitrate, 38.5 parts by mass of bismuth (III) oxide, and 20.6 parts by mass of antimony trioxide with 2,000 parts by mass of pure water at 60 ° C. as a solvent. In addition to the A1 liquid, A2 liquid was obtained by mixing 200.2 parts by mass of iron (III) nitrate nonahydrate and 515.1 parts by mass of cobalt (II) nitrate hexahydrate with 1,000 parts by mass of pure water. Next, A1 liquid and A2 liquid were mixed to obtain A liquid.

[0069] The obtained liquid A was heated to 95°C and stirred for 1 hour while maintaining the liquid temperature at 95°C to obtain liquid B. The obtained solution B was 10 3 Heat to ℃ and keep the liquid temperature at 10 3 The temperature was kept at °C and stirred for 3 hours to obtain solution C. The obtained solution C was dried in a spray dryer to obtain a dried product. The dried product was in a good dry state without adhering to the inner wall of the spray dryer. The dried product was first calcined at 300°C for 1 hour in an air atmosphere, and then pulverized. The calcined and pulverized dried product was then pressure-molded and crushed to obtain crushed particles. The crushed particles were then classified, and the crushed particles that passed through a sieve with a mesh size of 2.36 mm and did not pass through a sieve with a mesh size of 0.71 mm were collected. The collected crushed particles were then secondarily calcined at 500°C for 3 hours in an air atmosphere to obtain a catalyst. The composition of the obtained catalyst, excluding oxygen, was Mo 12 Bi 0.7 Fe 2.1 Co 7.5 W0.2 Sb 0.6 Cs 0.6 The catalyst was also subjected to ICP emission spectrometry and X-ray photoelectron spectroscopy. The calculated values ​​of A, B and B / A are shown in Table 1.

[0070] The catalyst thus obtained was then packed into a stainless steel reaction tube to form a catalyst layer, and an oxidation reaction of isobutylene was carried out under the following conditions. The results are shown in Table 1. Feed gas composition: 5% isobutylene, 12% oxygen, 10% water vapor, and 73% nitrogen. Reaction temperature: 340℃ Contact time between raw gas and catalyst: 2.7 seconds

[0071] <Example 2> Except for using 24.8 parts by mass of antimony trioxide, the A1 liquid was prepared in the same manner as in Example 1. In addition to the A1 liquid, the A2 liquid was prepared in the same manner as in Example 1. The A1 liquid and the A2 liquid were then mixed to obtain the A liquid. The obtained liquid A was heated to 95°C and stirred for 1 hour while maintaining the liquid temperature at 95°C to obtain liquid B. The obtained solution B was 10 3 Heat to ℃ and keep the liquid temperature at 10 3 The mixture was stirred for 5 hours while maintaining the temperature at °C to obtain solution C. The obtained solution C was dried in a spray dryer to obtain a dried product. The dried product was in a good dry state without adhering to the inner wall of the spray dryer. The resulting dried product was subjected to primary firing, molding and secondary firing in the same manner as in Example 1 to obtain a catalyst. The composition of the obtained catalyst, excluding oxygen, was Mo 12 Bi 0.7 Fe 2.1 Co 7.5 W 0.2 Sb 0.72 Cs 0.6 The catalyst was also subjected to ICP emission spectrometry and X-ray photoelectron spectroscopy. The calculated values ​​of A, B and B / A are shown in Table 1. Next, the obtained catalyst was used to carry out reaction evaluation in the same manner as in Example 1. The results are shown in Table 1.

[0072] <Example 3> Solution A1 was prepared in the same manner as in Example 1, except that the amount of antimony trioxide was changed to 15.5 parts by mass. Apart from the A1 solution, an A2 solution was prepared in the same manner as in Example 1. The A1 solution was then mixed with the A2 solution to obtain an A solution. The resulting liquid was heated to 95°C and stirred for 1 hour while maintaining the liquid temperature at 95°C to obtain liquid B. The obtained solution B was 10 3 Heat to ℃ and keep the liquid temperature at 10 3 The mixture was stirred for 7 hours while maintaining the temperature at °C to obtain solution C. The obtained solution C was dried in a spray dryer to obtain a dried product. The dried product was in a good dry state without adhering to the inner wall of the spray dryer. The resulting dried product was subjected to primary firing, molding and secondary firing in the same manner as in Example 1 to obtain a catalyst. The composition of the obtained catalyst, excluding oxygen, was Mo 12 Bi 0.7 Fe 2.1 Co 7.5 W 0.2 Sb 0.45 Cs 0.6 The catalyst was also subjected to ICP emission spectrometry and X-ray photoelectron spectroscopy. The calculated values ​​of A, B and B / A are shown in Table 1. Next, the obtained catalyst was used to carry out reaction evaluation in the same manner as in Example 1. The results are shown in Table 1.

[0073] <Comparative Example 1> Solution B was obtained in the same manner as in Example 1. The obtained solution B was dried in a spray dryer to obtain a dried product. That is, the step (iii) was not carried out, and the dried product was obtained by drying solution B. The dried product was in a good dry state without adhering to the inner wall surface of the spray dryer. The resulting dried product was subjected to primary firing, molding and secondary firing in the same manner as in Example 1 to obtain a catalyst. The composition of the obtained catalyst, excluding oxygen, was Mo 12 Bi 0.7 Fe 2.1 Co 7.5 W0.2 Sb 0.6 Cs 0.6 The catalyst was also subjected to ICP emission spectrometry and X-ray photoelectron spectroscopy. The calculated values ​​of A, B and B / A are shown in Table 1. Next, the obtained catalyst was used to carry out reaction evaluation in the same manner as in Example 1. The results are shown in Table 1.

[0074] <Comparative Example 2> Solution A was obtained in the same manner as in Example 1. The obtained solution A was heated to 95° C., and stirred for 2 hours while maintaining the solution temperature at 95° C. That is, in step (ii), the solution was stirred for a time longer than 90 minutes to obtain solution B′. The obtained solution B' was heated to 100°C and stirred for 1 hour while maintaining the solution temperature at 100°C to obtain solution C. The obtained solution C was dried in a spray dryer to obtain a dried product. The dried product was in a good dry state without adhering to the inner wall of the spray dryer. The resulting dried product was subjected to primary firing, molding and secondary firing in the same manner as in Example 1 to obtain a catalyst. The composition of the obtained catalyst, excluding oxygen, was Mo 12 Bi 0.7 Fe 2.1 Co 7.5 W 0.2 Sb 0.6 Cs 0.6 The catalyst was also subjected to ICP emission spectrometry and X-ray photoelectron spectroscopy. The calculated values ​​of A, B and B / A are shown in Table 1. Next, the obtained catalyst was used to carry out reaction evaluation in the same manner as in Example 1. The results are shown in Table 1.

[0075] [Table 1]

[0076] As shown in Table 1, in Examples 1 to 3 in which the catalysts having a B / A ratio within the specified range were used, the total selectivity for methacrolein and methacrylic acid was good. Methacrylic acid can be obtained by oxidizing the methacrolein obtained in this example, and methacrylic acid esters can be obtained by esterifying the methacrylic acid. [Industrial Applicability]

[0077] INDUSTRIAL APPLICABILITY The present invention can provide a catalyst capable of producing a target product such as an α,β-unsaturated aldehyde and / or an α,β-unsaturated carboxylic acid with high selectivity, and is therefore industrially useful.

Claims

1. A catalyst used in producing an α,β-unsaturated aldehyde and / or an α,β-unsaturated carboxylic acid from an alkene, an alcohol or an ether, comprising at least molybdenum and bismuth, a ratio of the amount of bismuth atoms to the amount of molybdenum atoms calculated by ICP (inductively coupled plasma) emission spectroscopy is A, and a ratio of a peak area of ​​bismuth atoms to a peak area of ​​molybdenum atoms measured by X-ray photoelectron spectroscopy is B, B / A is 1.5 to 4; The value of A is 0.02 to 0.1, The value of B is 0.04 to 0.2, A catalyst having a catalyst composition represented by the following formula (1): Mo a Bi b Fe c M d X e Y f Sig Oh (1) (In the formula (1), Mo, Bi, Fe, Si, and O represent molybdenum, bismuth, iron, silicon, and oxygen, respectively. M represents at least one element selected from the group consisting of cobalt and nickel. X represents at least one element selected from the group consisting of zinc, chromium, lead, manganese, calcium, magnesium, niobium, silver, barium, tin, tantalum, tungsten, antimony, phosphorus, boron, sulfur, selenium, tellurium, cerium, and titanium. Y represents at least one element selected from the group consisting of cesium, lithium, sodium, potassium, rubidium, and thallium. a, b, c, d, e, f, g, and h represent atomic ratios of each element, and when a=12, b=0.01 to 3, c=0.01 to 8, d=0.01 to 12, e=0.1 to 8, f=0.001 to 2, and g=0 to 20, and h represents the atomic ratio of each element. The oxygen atom ratio is required to satisfy the valence of each component.

2. 2. The catalyst according to claim 1, wherein the value of B / A is from 1.7 to 3.

3. The catalyst according to claim 1 or 2, wherein the value of B is from 0.07 to 0.

16.

4. A method for producing a catalyst containing at least molybdenum and bismuth and used in producing an α,β-unsaturated aldehyde and / or an α,β-unsaturated carboxylic acid from an alkene, an alcohol, or an ether, comprising the steps of: The method includes the following steps (i) to (v): (i) A step of mixing at least a molybdenum raw material and a bismuth raw material with a solvent to obtain a slurry (liquid A) (ii) A step of stirring the liquid A for 20 to 90 minutes at a temperature 1 to 30° C. lower than the boiling point of the solvent to obtain a slurry (liquid B). (iii) A step of stirring the liquid B for 10 minutes to 10 hours at a temperature 2° C. or more higher than the temperature of the step (ii) to obtain a slurry (liquid C). (iv) drying the C solution to obtain a dried product (v) calcining the dried product to obtain a catalyst The catalyst has a composition represented by the following formula (1): Mo a Bi b Fe c M d X e Y f Sig Oh (1) (In the formula (1), Mo, Bi, Fe, Si, and O respectively represent molybdenum, bismuth, iron, silicon, and oxygen; M represents at least one element selected from the group consisting of cobalt and nickel; X represents at least one element selected from the group consisting of zinc, chromium, lead, manganese, calcium, magnesium, niobium, silver, barium, tin, tantalum, tungsten, antimony, phosphorus, boron, sulfur, selenium, tellurium, cerium, and titanium; Y represents at least one element selected from the group consisting of cesium, lithium, sodium, potassium, rubidium, and thallium; a, b, c, d, e, f, g, and h represent atomic ratios of each element, and when a=12, b=0.01 to 3, c=0.01 to 8, d=0.01 to 12, e=0.1 to 8, f=0.001 to 2, and g=0 to 20; and h represents the atomic ratio of the preceding element. The oxygen atom ratio is required to satisfy the valence of each component.

5. The method for producing a catalyst according to claim 4, wherein in the step (i), 50 mass % or more of the total solvent is water.

6. The method for producing a catalyst according to claim 4 or 5, wherein the temperature in the step (iii) is 1 to 20° C. higher than the boiling point of the solvent.

7. The method for producing a catalyst according to any one of claims 4 to 6, wherein in the step (iii), the solution B is stirred for 90 minutes to 10 hours to obtain the solution C.

8. A method for producing an α,β-unsaturated aldehyde and / or an α,β-unsaturated carboxylic acid from an alkene, an alcohol or an ether by using the catalyst according to any one of claims 1 to 3.

9. A method for producing an α,β-unsaturated aldehyde and / or an α,β-unsaturated carboxylic acid from an alkene, an alcohol, or an ether, using a catalyst produced by the production method according to any one of claims 4 to 7.

10. A method for producing an α,β-unsaturated carboxylic acid, comprising producing an α,β-unsaturated carboxylic acid from an α,β-unsaturated aldehyde produced by the method according to claim 8 or 9.

11. A method for producing an α,β-unsaturated carboxylic acid ester, comprising producing an α,β-unsaturated carboxylic acid ester from the α,β-unsaturated carboxylic acid produced by the production method according to any one of claims 8 to 10.

Citation Information

Patent Citations

  • Production method for complex oxide catalyst

    JP2005169311A

  • Method of producing catalyst for producing unsaturated aldehyde and unsaturated carboxylic acid

    JP2011011099A

  • Catalyst for synthesizing unsaturated aldehyde and unsaturated carboxylic acid

    JP2011115681A

  • Catalyst for oxidative dehydrogenation of butene and method for producing same

    JP2020535002A

  • Metal oxide catalyst, and manufacturing method and manufacturing device for same

    WO2017208926A1

Cited By

  • Catalyst, method of producing catalyst, and α,β-unsaturated aldehyde, α,β-unsaturated carboxylic acid, and method of producing α,β-unsaturated carboxylic acid ester

    JP2025081757A